Biology Teachers' Perceptions of the Theory of Evolution Based on an Islamic Perspective in Senior High School - Destina, Ramanda; Chandra, Edy; Mulyani, Asep (Bioeducation Journal, 2025)
The theory of evolution is still debated today because it is considered to conflict with religious beliefs and teachings, especially concerning the origins of humans. Although many biology teachers believe that the theory of evolution is important and should be taught in schools, teachers' misconceptions about the theory can lead to misunderstandings and controversy. This study aims to identify the types of perceptions held by biology teachers who are Muslim and to describe the influence of Islamic perspectives on Muslim biology teachers' perceptions of the theory of evolution. This research employs a descriptive qualitative method. The subjects of this study are three Muslim biology teachers from a high school in Cirebon City. The results indicate that the teachers' perceptions fall into the category of Adam's Exceptionalism. Acceptance of the concept of evolution varies, and the Islamic perspective emphasizes that knowledge is a means to understand the greatness of Allah SWT and seek the truth. Teaching the theory of evolution in schools is considered important, and it should be conveyed correctly to prevent misconceptions.